Nutrient cycling in the Atlantic basin: The evolution of nitrate isotope signatures in water masses. Issue 10 (28th October 2015) - Tuerena, R. E.; Ganeshram, R. S.; Geibert, W.; Fallick, A. E.; Dougans, J.; Tait, A.; Henley, S. F.; Woodward, E. M. S.
Abstract: A basin‐wide transect of nitrate isotopes ( δ 15 NNO3, δ 18 ONO3 ), across the UK GEOTRACES 40°S transect in the South Atlantic is presented. This data set is used to investigate Atlantic nutrient cycling and the communication pathways of nitrogen cycling processes in the global ocean. Intermediate waters formed in the subantarctic are enriched in δ 15 NNO3 and δ 18 ONO3 from partial utilization of nitrate by phytoplankton and distant denitrification processes, transporting heavy isotope signatures to the subtropical Atlantic. Water mass modification through the Atlantic is investigated by comparing data from 40°S (South Atlantic) and 30°N (North Atlantic). This reveals that nitrate in the upper intermediate waters is regenerated as it transits through the subtropical Atlantic, as evidenced by decreases in δ 18 ONO3. We document diazotrophy‐producing high N:P particle ratios (18–21:1) for remineralization, which is further confirmed by a decrease in δ 15 NNO3 through the subtropical Atlantic. These modifications influence the isotopic signatures of the North Atlantic Deep Water (NADW) which is subsequently exported from the Atlantic to the Southern Ocean. This study reveals the dominance of recycling processes and diazotrophy on nitrate cycling in the Atlantic. These processes provide a source of low δ 15 NNO3 to the Southern Ocean via the NADW, to counteract enrichment in δ 15 NNO3 from water column denitrification in the Indo/Pacific basins. We hence identify the Southern Ocean as a key hub through which denitrification and N2 fixation communicate in the ocean through deepwater masses. Therefore, the balancing of the oceanic N budget and isotopic signatures require time scales of oceanic mixing. Key Points: Atlantic N cycling processes investigated using dual nitrate isotopes N recycling and high N:P remineralization observed in subtropics from N fixation NADW isotope signatures affected by subtropical Atlantic N recycling